Electronic Payment Cards and E-Commerce Upgrade - Mahdi, Ridda (Journal of Legal Studies and Researches, 2020)
In light of the successive and renewable technological developments that coincided with the efforts made by the Algerian state to improve and upgrade electronic commerce on the one hand and facilitate commercial transactions on the other hand. Modern technological technologies have had a prominent role in developing e-commerce performance. But in return, this can only be achieved in the framework of cooperation between all sectors, including the banking sector, which is an important link in the promotion of electronic commerce by activating its role in developing modern electronic payment methods.